Evaluation of the efficacy and safety of sarilumab combination therapy in patients with rheumatoid arthritis with inadequate response to conventional disease-modifying antirheumatic drugs or tumour necrosis factor α inhibitors: systematic literature review and network meta-analyses. Issue 1 (18th February 2019) - Choy, Ernest; Freemantle, Nick; Proudfoot, Clare; Chen, Chieh-I; Pollissard, Laurence; Kuznik, Andreas; Van Hoogstraten, Hubert; Mangan, Erin; Carita, Paulo; Huynh, Thi-Minh-Thao
Abstract : Objective: To compare efficacy and safety of subcutaneous sarilumab 200 mg and 150 mg every 2 weeks plus conventional synthetic disease-modifying antirheumatic drugs (+csDMARDs) versus other targeted DMARDs+csDMARDs and placebo+csDMARDs, in inadequate responders to csDMARDs (csDMARD-IR) or tumour necrosis factor α inhibitors (TNFi-IR). Methods: Systematic literature review and network meta-analyses (NMA) conducted on 24 week efficacy and safety outcomes: Health Assessment Questionnaire Disability Index, modified total sharp score (mTSS, including 52 weeks), American College of Rheumatology (ACR) 20/50/70, European League Against Rheumatism Disease Activity Score 28-joint count erythrocyte sedimentation rate (DAS28)<2.6; serious infections/serious adverse events (including 52 weeks). Results: 53 trials were selected for NMA. csDMARD-IR : Sarilumab 200 mg+csDMARDs and 150 mg+csDMARDs were superior versus placebo+csDMARDs on all outcomes. Against most targeted DMARDs, sarilumab 200 mg showed no statistically significant differences, except superiority to baricitinib 2 mg, tofacitinib and certolizumab on 24 week mTSS. Sarilumab 150 mg was similar to all targeted DMARDs. TNFi-IR: Sarilumab 200 mg was similar to abatacept, golimumab, tocilizumab 4 mg and 8 mg/kg intravenously and rituximab on ACR20/50/70, superior to baricitinib 2 mg on ACR50 and DAS28<2.6 and to abatacept, golimumab, tocilizumab 4 mg/kg intravenously and rituximab on DAS28<2.6. Sarilumab 150 mg was similar to targeted DMARDs but superior to baricitinib 2 mg and rituximab on DAS28<2.6 and inferior to tocilizumab 8 mg on ACR20 and DAS28<2.6. Serious adverse events, including serious infections, appeared similar for sarilumab versus comparators. Conclusions: Results suggest that in csDMARD-IR and TNFi-IR (a smaller network), sarilumab+csDMARD had superior efficacy and similar safety versus placebo+csDMARDs and at least similar efficacy and safety versus other targeted DMARDs+csDMARDs.